1977
DOI: 10.4141/cjas77-068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alfalfa Consumption on Estrogen Levels in Ewes

Abstract: (Guggolz et al. 196l). The levels of can have plasma levels of 5 ng coumesphyto-estrogens found in alfalfa are geo-trol/ml (Lindner 1967

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Kelly et al (1976) noted that very high levels of coumestans inhibited the expression of oestrus in ewes and suggested that this was due to a lack of endogenous oestrogen. Newsome & Kitts (1977) reported that ewes consuming forage containing phyto-oestrogens had plasma levels of oestrogen that were lower and more uniform than those ofcontrol sheep, suggesting an effect on the secretion of gonadotrophins.…”
Section: Introductionmentioning
confidence: 95%
“…Kelly et al (1976) noted that very high levels of coumestans inhibited the expression of oestrus in ewes and suggested that this was due to a lack of endogenous oestrogen. Newsome & Kitts (1977) reported that ewes consuming forage containing phyto-oestrogens had plasma levels of oestrogen that were lower and more uniform than those ofcontrol sheep, suggesting an effect on the secretion of gonadotrophins.…”
Section: Introductionmentioning
confidence: 95%
“…Natural dietary exposures to phytoestrogens have been associated with cystic ovaries, irregular estrus, and anestrus in cattle (91), and reduced breeding success in California quail (92). Compromised follicular development (91) and reductions in luteal phase plasma progesterone and E 2 , as well as shortened luteal phases, have been reported in cycling ewes whereas increases in estradiol and cortisol have been reported in pregnant ewes (93,94). Soy isoflavone diets providing doses of 1 mg/kg/day were associated with infertility in captive cheetahs (95).…”
Section: Ovarian Cyclicitymentioning
confidence: 99%
“…Newsome and Kitts (1977) [123] showed that ewes fed on lucerne had higher levels of phytoestrogen in their plasma and lower levels of endogenous oestrogens than ewes fed grass (Dactylis glomerata), suggesting that gonadotropin stimulation of the ovary was reduced by the presence of phytoestrogen in the plasma. With coumestrol in white clover, Sanger and Bell (1959) [19] found it affected fertilisation but not ovulation.…”
Section: Suppression Of Oestrusmentioning
confidence: 99%